Memória e conflitos: um estudo das contradições na edificação do passado santo-angelense - Lucca, Laura Perin (2023)
That memory and legal principles clash in the field of heritage is clear even from a inattentive observation of the heritage scene in any locality. But, if the built historical heritage is, as the legal documents claims, any building classified as of significant importance by some arm of the State, if this is so, why does a county like Santo Ângelo/RS (Brazil), which has legislative statements at all heritage levels – local, state, national and international – have difficulties in guaranteeing the preservation of listed protected cultural properties? What makes something memorable, why and for whom? In order to understand the contradictions of the heritage scene, the disputes over organized memory and identity from Missões, I propose a documentary study of heritage disputes in the county of Santo Ângelo. This is because the location is ideal for this research, its medium size facilitates the identification of conflicts between the narrated life story and the specific memory resulting from the memory framing work undertaken due to the recognition of the location as heritage by the authorities. Here I ask, what makes it possible to understand the legitimacy of legislative heritage statements in practice? If and by whom are these appointments recognized? Whose interest, are they? There is undoubtedly a latent rationality that guides the public disputes between agents against or in favor of patrimonialization. It is the purpose of this research to identify the roots of these contradictions and therefore the disputes over what should or shouldn’t be considered memorable in the county